Rheological and textural properties of acid-induced soybean protein isolate gel in the presence of soybean protein isolate hydrolysates or their glycosylated products. (30th October 2021) - Li, Lin; He, Hui; Wu, Daize; Lin, Derong; Qin, Wen; Meng, Demei; Yang, Rui; Zhang, Qing
Highlights: Enzymatic hydrolysis and glycosylation of soybean protein isolate (SPI) are studied. Addition of 0.5% and 0.75% (w/v) SPI hydrolysates weakens gel properties of SPI. Glycosylation reduces the adverse effect of hydrolysates on the formation of SPI gel. Glycosylated hydrolysates-added gels showed a lower stiffness than SPI gel. Abstract: Enzymatic hydrolysis and glycosylation were successively applied to modify soybean protein isolate (SPI) and rheological and textural properties of acid-induced SPI gel added with the obtained SPI hydrolysates and their glycosylated products were then investigated. The incorporation of SPI hydrolysates decreased the elastic modulus (G′) and hardness of SPI gel, which might be related to the random aggregation between SPI hydrolysates and native SPI molecules via hydrophobic interactions. In addition, as the molecular weight of SPI hydrolysates decreased, the reduction in G′ and hardness became more significant. Although glycosylation of SPI hydrolysates weakened the adverse effects of hydrolysates on the SPI gel formation to some extent, the glycosylated SPI hydrolysates were still unable to improve the gel quality compared with the control. However, results of this research may provide important information for understanding the influencing mechanism of SPI hydrolysates and their glycosylated products on the formation of SPI gel.